2012
DOI: 10.1111/j.1600-9657.2012.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage media enhance osteoclastogenic potential of human periodontal ligament cells via RANKL‐independent signaling

Abstract: PDL cells kept in the three storage media led to TRAP+ multinucleated, osteoclast-like cells formation via RANKL-independent signaling. The ability to induce osteoclastogenesis may be considered as one of the factors to evaluate the ability of storage medium to maintain PDL viability after tooth avulsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
13
0
1
Order By: Relevance
“…Cell culture media such as MEM and DMEM have been used as storage media for avulsed teeth. 17,[43][44][45] DMEM is recommended for the short-and long-term storage of avulsed teeth because it contains two to four times more glucose, four times more amino acid and vitamin than MEM. However, DMEM and Ham's F12…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture media such as MEM and DMEM have been used as storage media for avulsed teeth. 17,[43][44][45] DMEM is recommended for the short-and long-term storage of avulsed teeth because it contains two to four times more glucose, four times more amino acid and vitamin than MEM. However, DMEM and Ham's F12…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a report by Zhan et al. showed that PGE2 treatment in cocultures of periodontal ligament cells and osteoclasts is involved in osteoclastogenesis. In this study, the expression levels of bone‐resorptive cytokines (IL‐1β, IL‐6, PGE2, and TNF‐α) in each group were determined by RT‐PCR and ELISA.…”
Section: Discussionmentioning
confidence: 99%
“…The microarray data at 3 h of exposure to milk showed 1213 upregulated genes and 569 downregulated genes with biologically well-characterized protein function (Tables 2 and 3). Additionally, PDL cells kept in the following three storage media: HBSS, milk, and a-MEM led to TRAP+ osteoclast-like multinucleated cell formation via RANKL-independent signaling (22). Furthermore, several chemokines are expressed in periodontal tissue diseases, for example CCL2 (CCR1 ligand), CCL3 (CCR1 and CCR5 ligand), CCL5 (CCR1 and CCR5 ligand), and CCL20 (CCR6 ligand) (21).…”
Section: Discussionmentioning
confidence: 99%